Pengaruh Beban Kerja dan Kompensasi Kerja Terhadap Kepuasan Kerja Karyawan CV. Soso Alsera Murni Jombang - Siska Mariana; Khotim Fadhli (Jurnal Manajemen Bisnis Era Digital, 2025)
Job satisfaction in a company has an important impact, not only for employees, but also for the company itself. Job satisfaction is an important aspect to support work productivity. Given that each employee has different characteristics, the level of job satisfaction also varies, and these differences can have various impacts. This study aims to examine how workload and work compensation affect the level of employee job satisfaction. The population and sample were 81 employees of CV. Soso Alsera Murni Jombang, using a saturated sample technique. This study applies a quantitative approach through the distribution of questionnaires and analyzed using multiple linear regression. The results of the study revealed that workload had no effect on job satisfaction, while compensation had a positive and significant effect on job satisfaction. Simultaneously, workload and work compensation had a significant effect on employee job satisfaction at CV. Soso Alsera Murni Jombang.